Speech of the Right Honorable Nicholas Vansittart, Chancellor of the Exchequer, in the House of Commons, February 20, 1815, in the Committee of Ways and Means (The Pamphleteer, 1815)
The Pamphleteer ; vol. VI, no. XI, p. 2-26. - First published with various revisions and corrections in the Pamphleteer. - With : The budget for 1815.